Cytokines as an important player in the context of CAR-T cell therapy for cancer: Their role in tumor immunomodulation, manufacture, and clinical implications - Silveira, Caio Raony Farina; Corveloni, Amanda Cristina; Caruso, Sâmia Rigotto; Macêdo, Nathália Araújo; Brussolo, Natália Moscheta; Haddad, Felipe; Fernandes, Taisa Risque; de Andrade, Pamela Viani; Orellana, Maristela Delgado; Guerino-Cunha, Renato Luiz (Frontiers in Immunology, 2022)
CAR-T cell therapies have been recognized as one of the most advanced and efficient strategies to treat patients with hematologic malignancies. However, similar results have not been observed for the treatment of solid tumors. One of the explanations is the fact that tumors have extremely hostile microenvironments for the infiltration and effector activity of T-cells, mainly due to the presence of highly suppressive cytokines, hypoxia, and reactive oxygen species. Taking advantage of cytokines functionally, new fourth-generation CAR constructs have been developed to target tumor cells and additionally release cytokines that can contribute to the cytotoxicity of T-cells. The manufacturing process, including the use of cytokines in the expansion and differentiation of T cells, is also discussed. Finally, the clinical aspects and the influence of cytokines on the clinical condition of patients, such as cytokine release syndrome, who receive treatment with CAR-T cells are addressed. Therefore, this review aims to highlight how important cytokines are as one of the major players of cell therapy.